Determinants of Youth Digital Political Participation in Civic-Oriented Information Systems: An Empirical Study in the Context of Digital Democracy in Indonesia - Irma Yurni; Arief Rahman; Muhammad Hatta; Fakhrurrazi Fakhrurrazi; Ella Dewi Latifah; Eka Jayadiputra (Sisfo: Jurnal Ilmiah Sistem Informasi, 2026)
This study investigates the determinants of youth digital political participation in Civic-Oriented Information Systems (COIS) within the context of digital democracy in Indonesia by extending the Unified Theory of Acceptance and Use of Technology (UTAUT) with psychopolitical variables. Although young people demonstrate high levels of internet usage, their engagement in institutional digital platforms remains relatively low, indicating a persistent gap between digital access and substantive civic participation. A quantitative explanatory design was employed, involving 214 respondents aged 17–30 selected through purposive sampling. Data were collected through an online survey and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The measurement and structural models were evaluated through reliability, validity, bootstrapping (5,000 subsamples), and predictive relevance testing. The results show that Performance Expectancy is the strongest predictor of participation intention, followed by Political Self-Efficacy and Institutional Trust. Facilitating Conditions and Effort Expectancy also have significant positive effects, while Perceived Risk negatively influences participation intention. Social Influence is not statistically significant, whereas Digital Literacy significantly moderates the relationship between Performance Expectancy and Participation Intention, strengthening the effect of perceived usefulness on behavioral intention. The model explains 61.2% of the variance in participation intention (R² = 0.612), indicating strong explanatory power. The study concludes that youth participation in COIS is shaped by both technological and psychopolitical factors. It contributes theoretically by integrating psychopolitical dimensions into the UTAUT framework and offers practical implications for improving transparency, strengthening political efficacy, and reducing perceived risks in digital governance systems.